2019
DOI: 10.1002/smll.201904774
|View full text |Cite
|
Sign up to set email alerts
|

Highly Morphology‐Controllable and Highly Sensitive Capacitive Tactile Sensor Based on Epidermis‐Dermis‐Inspired Interlocked Asymmetric‐Nanocone Arrays for Detection of Tiny Pressure

Abstract: The tactile sensor lies at the heart of electronic skin and is of great importance in the development of flexible electronic devices. To date, it still remains a critical challenge to develop a large-scale capacitive tactile sensor with high sensitivity and controllable morphology in an economical way. Inspired by the interlocked microridges between the epidermis and dermis, herein, a highly sensitive capacitive tactile sensor by creating interlocked asymmetric-nanocones in poly(vinylidenefluorideco-trifluoroe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
159
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(160 citation statements)
references
References 67 publications
1
159
0
Order By: Relevance
“…The presence of microstructures results in a fast response and high sensitivity (Figure 4h). [107] Microstructures expand the air gap between the electrodes, and the dielectric layer is highly influenced by deformation. For instance, Wu et al reported all-fabric with a wireless battery-free monitoring system; the capacitance pressure sensor shows a high sensitivity of 0.283 KPa À1 .…”
Section: Structures Designsmentioning
confidence: 99%
“…The presence of microstructures results in a fast response and high sensitivity (Figure 4h). [107] Microstructures expand the air gap between the electrodes, and the dielectric layer is highly influenced by deformation. For instance, Wu et al reported all-fabric with a wireless battery-free monitoring system; the capacitance pressure sensor shows a high sensitivity of 0.283 KPa À1 .…”
Section: Structures Designsmentioning
confidence: 99%
“…To enhance the sensitivity, researchers have explored various solutions such as using micro pillars, microcones, micro pyramid, micro cones, and/or bionic patterns etc. [25][26][27][28][29][30]. These approaches have yielded interesting results but understanding the role of dielectric material properties such as their stiffness is also an important factor that is needed to be explored to reproduce the mechanoreceptors sensing capability [16].…”
Section: State Of the Artmentioning
confidence: 99%
“…Sensing technology has experienced a rapid growth, by extending the power of natural senses, over the past decades. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In particular, measurements of external mechanical force or pressure at a surface, inspired by human sense of touch, have already been employed in a wide range of industrial, medical, and consumer applications. Historically, this category of the sensing devices has been called a pressure sensor when gauging into fluidic objects (either liquid or air), or force sensors in contact with solid objects.…”
Section: Introductionmentioning
confidence: 99%